Al-Ghazali's Educational thought Model (Islamic Educational Philosophical Approach) - Imam Hanafi; Hanifatur Rizqi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Al-Ghazali is one of the leaders of Muslim scientists who thought to be reckoned with in the world of science. But even so, thought a scientist would never be separated from the pros and cons. Some have claimed that Islam had reached its heyday in around the 7th century / M decline. The circles say that Al-Ghazali considered most responsible for it, because of changing patterns of Muslim life at that time to go back to the ascetic. However, Al-Ghazali thinking about education is one of the perfect reference. Because Al-Ghazali restrict education with the mystical thought.